2019
DOI: 10.1038/s41598-019-52240-3
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric switching in ferroelastic materials with rough surfaces

Abstract: Electric switching of non-polar bulk crystals is shown to occur when domain walls are polar in ferroelastic materials and when rough surfaces with steps on an atomic scale promote domain switching. All domains emerging from surface nuclei possess polar domain walls. The progression of domains is then driven by the interaction of the electric field with the polarity of domain boundaries. In contrast, smooth surfaces with higher activation barriers prohibit effective domain nucleation. We demonstrate the existen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…The energy of avalanches in Barkhausen noise is partially released by elastic waves during acoustic emission, AE. As AE measurements have unsurpassed sensitivity they became the method of choice for the investigation of field induced changes in ferroics and are hence at the heart of current research into the dynamics of switching processes 2,13,14,[17][18][19][20][21][22]30,[32][33][34][35][36] . Here we show why some results of AE deviate from the predictions of mean field theory, MFT 14,37 .…”
Section: Acoustic Emission (Ae) Measurements Of Avalanches In Differementioning
confidence: 99%
“…The energy of avalanches in Barkhausen noise is partially released by elastic waves during acoustic emission, AE. As AE measurements have unsurpassed sensitivity they became the method of choice for the investigation of field induced changes in ferroics and are hence at the heart of current research into the dynamics of switching processes 2,13,14,[17][18][19][20][21][22]30,[32][33][34][35][36] . Here we show why some results of AE deviate from the predictions of mean field theory, MFT 14,37 .…”
Section: Acoustic Emission (Ae) Measurements Of Avalanches In Differementioning
confidence: 99%
“…Known as domain boundary engineering, ferroelastic materials can be functionalized by designing and optimizing domain walls 1,2 . Many studies have observed that interface possess properties that do not exist in bulk, such as the superconductivity [3][4][5] , ferroelectricity 6,7 . For example, twin walls are known to be superconductive in WO 3-x 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Another critical aspect will be a detailed understanding of the control of the walls' position and motions by means of electric or elastic stress fields. The effect of electric fields on ferroelastic wall motions 89,90 and more generally the control of domain wall dynamics (BOX 2) will be the key.…”
Section: Ferroelastics and Non-polar Materialsmentioning
confidence: 99%